ANALISIS PERSEPSI MASYARAKAT TENTANG LAYANAN PEMBIAYAAN BERBASIS TEKNOLOGI INFORMASI BERDASARKAN PRINSIP SYARIAH (Studi Pada Desa Situ Udik Kecamatan Cibungbulang Kabupaten Bogor) - Muhammad Rifal Arrifqi; Rully Trihantana; Ria Kusumaningrum (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2021)
ABSTRACT The purpose of this study was to determine the knowledge and public perception of digital-based (online) financing services based on sharia principles. the method used is descriptive qualitative. The primary data in this study are the people of Situ Udik Village, Cibungbulang District, Bogor, while the secondary data is in the form of information obtained from the internet, books, journals, articles and other literature. Based on the results of the study, it can be concluded that most (70%) people do not know about digital-based services (online) based on sharia principles. In addition, the analysis of public perception in terms of needs (48%) of the community is quite in need and when viewed from the perspective of interest (44%) the community is quite concerned with using digital-based (online) financing services based on sharia principles. with the perception to avoid the practice of usury and avoid the frauds that occur in conventional credit. In this case, it is necessary to increase socialization and the existence of facilitators to increase public awareness in order to avoid the practice of usury..